The Role of the Church and Christian Religious Education in Post-Conflict Social Recovery in the Local Context of Rongkong - Jodih Jodih (Harati: Jurnal Pendidikan Kristen, 2025)
The Rongkong area in North Luwu carries historical wounds due to the DII/TI rebellion, leaving prolonged social and spiritual trauma. This study aims to critically analyze the role of the Church and Christian Religious Education (CRE) in the process of trauma healing, social reconciliation, and sowing hope post-conflict. Using a qualitative descriptive approach, data were collected through literature review, in-depth interviews with church leaders and community members, as well as limited participatory observation. The study is grounded in the theoretical framework of memory theology (Johann Baptist Metz and Paul Ricoeur) and critical pedagogy (Paulo Freire), emphasizing the importance of collective memory and liberating education within the context of historical wounds. The findings indicate that the church acts as a healing community through liturgy, pastoral care, and social advocacy, while CRE serves as a transformative space that builds historical awareness, spirituality of forgiveness, and intergenerational participation in reconciliation. This article offers theological-pedagogical reflections and contextual praxis for the church and Christian educators in nurturing memory and fostering hope within post-conflict communities.